PATENT: A JOURNEY FROM IDEA TO PATENT - Gupta, Sonu; Bansal, Ravinder Nath; Sodhi, Surender Pal Singh; Brar, Gursimrat Kaur; Bansal, Ruchika (Innoriginal: International Journal of Sciences, 2018)
Indian patent system is strengthened by stringent rules which have been amended from time to time. Patent system encourages for invention and disclosure to the public so that other can benefit from that invention. The patent has a significant role in ayurveda, yoga, siddha, unani, dental as well as medical sciences. Difficulties arise due to a complex system of patent which acts as a barrier for inventors. Further, the situation is complicated by the lack of knowledge regarding the procedure of filing and search patent application. This paper attempts to simplify these difficulties and answer various queries arising in mind of an inventor. Key words: Patent, Patentable invention, Patent application, Invention, Patent search.